Oxidation of the silicon terminated (1 0 0) diamond surface. (14th November 2016) - Schenk, A K; Sear, M J; Tadich, A; Stacey, A; Pakes, C I
Abstract: The oxidation of the silicon terminated (1 0 0) diamond surface is investigated with a combination of high resolution photoelectron spectroscopy, low energy electron diffraction and near edge x-ray absorption fine structure spectroscopy. The effects of molecular O 2 and H 2 O dosing under UHV conditions, as well as exposure to ambient conditions, have been explored. Our findings indicate that the choice of oxidant has little influence over the resulting surface chemistry, and we attribute approximately 85% of the surface oxygen to a peroxide-bridging arrangement. Additionally, oxidation does not alter the silicon–carbon bonding at the surface and therefore the ( 3 × 1 ) reconstruction is still present.